2022
DOI: 10.5603/cj.a2020.0134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hypertonic saline solutions fluid resuscitation on hypovolemic shock: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Fluid resuscitation is a fundamental intervention in patients with hypovolemic shock resulting from trauma. Appropriate fluid resuscitation in trauma patients could reduce organ failure, until blood components are available, and hemorrhage is controlled. We conducted a systematic review and meta-analysis assessing the effect of hypertonic saline/dextran or hypertonic saline for fluid resuscitation on patient outcomes restricted to adults with hypovolemic shock. Methods: We conducted a search of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…However, we noticed that the mortality rate in HSD seems to be lower as opposed to isotonic crystalloid (21.2% vs.24.4%), suggesting that HSD might have a signi cant improvement in mortality in the future with more randomized trials. Contrary to our nding, a previous systematic review comparing HSD to isotonic crystalloids among patients with hypovolemic shock found that HSD was associated with a signi cant reduction in overall mortality (p = 0.01) [31]. The discrepancy between our ndings and this systematic review can be attributed to our analysis having more randomized trials, which mostly did not show the mortality bene t of HSD over isotonic crystalloids.…”
Section: Colloids Versus Crystalloidscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we noticed that the mortality rate in HSD seems to be lower as opposed to isotonic crystalloid (21.2% vs.24.4%), suggesting that HSD might have a signi cant improvement in mortality in the future with more randomized trials. Contrary to our nding, a previous systematic review comparing HSD to isotonic crystalloids among patients with hypovolemic shock found that HSD was associated with a signi cant reduction in overall mortality (p = 0.01) [31]. The discrepancy between our ndings and this systematic review can be attributed to our analysis having more randomized trials, which mostly did not show the mortality bene t of HSD over isotonic crystalloids.…”
Section: Colloids Versus Crystalloidscontrasting
confidence: 99%
“…Our meta-analysis has shown that even though the mortality rate was lower in hypertonic crystalloid groups (20% vs. 23%), the difference compared to isotonic crystalloids was statistically insigni cant (p = 0.60). This nding is supported by a previous systematic review, which found no signi cant difference among hypovolemic shock patients resuscitated with hypertonic saline or isotonic saline (OR: 0.90; 95% CI: 0.66-1.23; p = 0.51) [31]. Moreover, we found no signi cant difference in the amount of blood products transfused within the rst 24 hours, suggesting that hypertonic crystalloids are as effective as isotonic crystalloids in resuscitating hypovolemic shock patients.…”
Section: Hypertonic Crystalloids Versus Isotonic Crystalloidssupporting
confidence: 73%
“…Currently, there is an active search for optimal ways to create new wound-healing drugs with a better balance of regenerative and antimicrobial effect of a new type that does not cause antibiotic resistance. Great hopes are placed on nanocomposites based on cerium oxide nanoparticles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], which is a rare earth metal with variable valence, coated with a polymer shell, dextran [ 50 , 51 , 52 , 53 , 54 ], which is widely used in medicine [ 67 , 68 , 69 ]. This complex seems to be an excellent combination for the development of a medical drug that effectively accelerates wound healing.…”
Section: Discussionmentioning
confidence: 99%